Experiment research on friction coefficient between a steel plate and rail in transient sliding thermal contact through a pendulum - Yunpeng Wei; Yaping Wu; Kun Chen; Anyuan Sun (Results in Physics, 2018)
The main goal of this article is to study the friction coefficient of wheel/rail transient sliding thermal contact through a pendulum. A new method is firstly established to analyze the friction coefficient. The formula for calculating the friction coefficient is not dependent on material and thermal parameters of wheel/rail. The experiment measures the sliding contact time and friction coefficient at different wheel temperature. The results show that the sliding contact time is very short and the average sliding contact time is 8 ms. The friction coefficient slowly ascends before 500 °C and then gradually decreases from 500 °C to 1000 °C. From 1000 °C to 1200 °C, the friction coefficient quickly descends. The maximum friction coefficient is 0.388. With the increase of wheel temperature, the number of small pits gradually decreases, and the scratching on the wheel surface becomes more obvious. Keywords: Friction coefficient, Temperature, Sliding contact, Contact time